AVALIAÇÃO DA QUALIDADE FÍSICA DO SOLO NA ÁREA EXPERIMENTAL DA UEMS DE MUNDO NOVO - SOUZA, Durval Kauê de Almeida; OZORIO, Jefferson Matheus Barros; CUNHA, Vinicius Estigarribia; CASTILHO, Selene Cristina de Pierri; MARRA, Leandro Marciano (ANAIS DO ENIC, 2025)
-